Analisis Kesulitan Belajar Bahasa Arab Maharah Istima’ - Fitriyah, Khoirun Nisa'il (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2021)
Arabic is a science that cannot be left behind in the world of pesantren, because language is the heart of knowledge for students to deepen their religious knowledge in Islamic boarding schools. To master Arabic, there are two stages that must be mastered by students, namely; Arabic language skills and Arabic language skills. But in this study, the researcher explores the Arabic language skills possessed by students at the Sabilul Muttaqin Mojokerto Islamic boarding school, namely Listening skills. So that the researcher raised the title of the analysis of the difficulties of the students in Mastering Listening Skills in Arabic subjects. This research is descriptive qualitative, data collection methods use observation, interviews and documentation. The analysis technique uses data reduction, data presentation and making data conclusions. Conclusion From the results of this study are; first, students have difficulty accepting or hearing conversations in Arabic because of the influence of different speech styles. Second, the students' weak ability to understand the meaning of the accepted sentence, so students need to be repeated many times. Third, requires a great concentration in understanding the Arabic sentence that is heard. Keywords: Learning difficulties, listening skills.